Effects of synthetics cathinons: systematic review (Academic Journal of Internal Affairs, 2023)
Aim: The aim of the study is to explore the mechanisms of action and pharmacological effects of the new type of synthetic cathinones by a systematic review of the relevant literature.Methodology: A topic-oriented systematic literature review was conducted, focusing on exploratory studies closely related to the topic. The sample of publications included the most relevant studies, reported primary research results of empirical studies (n = 24).Findings: The results of studies using self-administration, discriminative stimulation, locomotor activity and conditioned place preference tests clearly demonstrate, with some exceptions, the aversive and addictive potential and psychostimulant effects of synthetic cathinone derivatives. Some synthetic cathinones also induce significant changes in the diversity of the gut microbiome, and mutagenic effects on DNA cannot be excluded in some of them, which may cause serious problems in the long term.Value: The paper is the first to summarise in Hungarian the current results of empirical studies on synthetic cathinones. The presented results may be useful not only for the experts of medical and health sciences, but also for the member of law enforcement profession and police science.
Keywords: synthetic cathinones; DNA; illegal drug market; self-administration